Reaktualisasi Kompetensi Sosial Guru dalam Ekosistem Pembelajaran Digital - Beby Mariyani; Dela Nopita; Ahmad Zainuri; Frika Fatimah Zahra (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
This article examines the re-actualization of teachers’ social competence within the digital learning ecosystem. The rapid development of technology has transformed conventional learning into digital-based environments, which significantly affect the patterns of interaction between teachers and students. This transformation often leads to reduced direct communication, emotional connection, and social engagement in the learning process. Therefore, this study aims to explore the importance of strengthening teachers’ social competence and to identify strategies for its re-actualization in digital learning contexts, particularly in early childhood education. This study uses a qualitative approach through a literature review by analyzing relevant journals, books, and scientific articles published in recent years. The findings indicate that teachers’ social competence remains a crucial factor in creating meaningful learning, even in virtual environments. Effective communication, empathy, and interactive engagement must be adapted to digital platforms. The study also highlights several strategies, such as integrating humanistic approaches, optimizing interactive media, and enhancing digital communication skills. These findings imply that strengthening teachers’ social competence is essential to support effective and holistic learning in the digital era.